Pengembangan Program Komputer untuk Pemilihan Kincir Angin Pembangkit Tenaga Listrik di Pedsaan - Rusnia Zaidun; Mad Yamin (PERTETA, 2010)
Abstract Rural areas which have not getting electricity networks provided by Perusahaan Listrik Negara or PLN can consider constructing windmills to generate electricity. In the construction of these windmills, a special attention should be paid to such factors as topography of the location and wind speed in the site of windmills so that a proper type of windmills that will be used in the area can be decided. Therefore, developing a computer program for selecting the type of windmills used is expected to serve as an input for the development of agricultural technologies that utilize renewable energy. Making the computer program consists of the following steps: making the initial view layout of the program, program scripts, animation, and program evaluation. Making a program design is started by determining the input and output components of the program so as to set the initial view of the program. Based on the formulas used for windmills generating electricity, a computer program to determine the type of windmills was developed by using Visual Basic 6.0. Meanwhile, Adobe Flash CS3 Professional software was used to construct animated windmills, which can also be run under Visual Basic 6.0 program.Keywords: windmill, energy, electricity, power Diterima: 13 Maret 2010; Disetujui: 17 September 2010